EMBLICA OFFICINALIS (AMLA): A PROSPECTIVE REVIEW ON DISTINCTIVE PROPERTIES AND THERAPEUTIC APPLICATIONS OF AMLA - HASSAN, SYEDA MONA; MUGHAL, SHAHZAD SHARIF; ASLAM, ASMA; MUSHTAQ, MARYAM; MUNIR, MUNEEZA; PERVEZ, SUMAIRA; SHABBIR, NAGEENA; AYUB, ALI RAZA; FARMAN, MUHAMMAD (Innovare Journal of Ayurvedic Sciences, 2020)
Phyllanthus emblica Linn. (Emblica officinalis Gaertn.) usually referred as Amla is well-known tree used for the production of herbal as well as pharmacological medicines. It is a famous truth so as to every components of Amla are beneficial for the treatment of numerous illnesses. Among all, the maximum vital element is fruit. Amla fruit is extensively utilized in all around the world gadget of medication as antioxidant, hepatoprotective, nephroprotective, metabolic syndrome, cardioprotective, hair energizer, stomach ulcer protective, and sickness, as by myself or in aggregate with different herbs. The different researches show that it contains large number of biochemical components, especially alkaloids, phenols, tannins, multivitamin, and inorganic compounds. The organic chemical constituents present in Amla involve ellagic acid, gallic acid, emblicanin A and B, phyllembein, quercetin, and ascorbic acid are decided to be efficient for health. The review articles related to Amla well known its palliative, anti-coughing, anti-atherogenic, immune booster, aerobic, intestinal protective, kidney protective, and neuroprotective, chemopreventive, radio modulatory, and anticancer homes. It is also stated to possess amazing unfastened radical scavenging, oxidation inhibitor, anti-inflammatory, antimutagenic, and immune modulatory sports that are effectual inside the remedy and treatment of diverse illnesses such as cancer, atherosclerosis, diabetes, liver, and coronary heart illnesses. In this text, we communicate the nutritional fee, biochemical components, and conventional makes use of medicinal cost of Amla and its use as a household treatment. We, moreover, emphasized the mechanisms entails in pharmacological sports based on the modern-day research critiques and attempted to summarize the results of studies carried out from the beyond 5 years with proper specifications on the destiny possibilities in a pharmacological perspective.